Thematic foundations of Ján Kalinčiak’s poem “Králik [The wren]” - Marta Fülöpová (Slovenska Literatura, 2023)
Ján Kalinčiak (1822 – 1871) wrote his poem “Králik [The wren]” (1840) early in his career. The poem connects two different thematic and generic components – the allegorical and satirical social poem depicting the course of elections and the genre of the etymological fable which explains the origin of a name of a bird. In trying to identify the possible starting points of the two thematic layers, it turns out that the allegorical connection of the bird parliament with the portrayal of elections in Hungary had appeared in the unpublished satirical dramatic dialogue by the Hungarian author Ádám Pálóczi Horváth (1760 – 1820), “Az üstökös csillag befolyása a madár társadalom éghajlatára” ([The influence of the comet on the climate of the bird society] 1819). The dialogue described the course of the 1819 election in Zala county. The article traces common elements in the texts of the two authors. Kalinčiak’s poetic treatment of the story of the eagle and the wren suggests its double interpretation: it is both a moralising fable about the victory of the weak over the strong and an etymological fable about the origin of the name of a small bird.